Existence and Nonexistence of Positive Solutions for a Higher-Order Three-Point Boundary Value Problem - Yongping Sun; Qian Sun; Xiaoping Zhang (Abstract and Applied Analysis)
This paper is concerned with the existence and nonexistence of positive solutions for a nonlinear higher-order three-point boundary value problem. The existence results are obtained by applying a fixed point theorem of cone expansion and compression of functional type due to Avery, Henderson, and O’Regan.